Nutrition of children with delay of four domestic growth - A. F. Kiosov (Лечащий Врач, 2021)
One of the important issues in the organization of nursing of children with intrauterine growth retardation (IUGR) is the issue of organizing enteral feeding. Enteral nutrition approaches in children differ depending on the degree of maturity of the child. Currently, the most detailed approaches to enteral feeding in premature infants with IUGR are reflected. In the diet of such children, as a rule, special therapeutic products are used: breast milk fortifiers and/or mixtures for premature and low-weight babies. In modern literature, there is little data on the characteristics of the organization of enteral feeding in full-term children with IUGR. The article discusses the issues of feeding full-term newborns with IUGR with a lack of breast milk, as well as the possibility of using a specialized mixture for low-weight children for feeding in such children.